KOMPARASI PERFORMA INFRASTRUKTUR WORDPRESS PADA DIGITALOCEAN (CLOUD) DAN VMWARE WORKSTATION (ON-PREMISES) - Ahkam, Mizanul; Bakar, Abu; Kurniawati, Kurniawati (Jurnal Teknik Informasi dan Komputer (Tekinkom), 2025)
This study evaluates the performance of WordPress infrastructure on two different hosting platforms: DigitalOcean VPS (cloud) and VMware Workstation (on-premises). The research aims to compare key performance metrics including Time to First Byte (TTFB), Largest Contentful Paint (LCP), Fully Loaded Time, Cumulative Layout Shift (CLS), and overall page speed score. Identical WordPress installations (version 6.8.1, Twenty Twenty-Five theme, no caching plugins) were deployed on both platforms using Debian 12 and LAMP stack. Performance was tested using SpeedVitals (Jakarta, desktop), WebPageTest (Singapore, Chrome), and Google PageSpeed Insights (mobile). Results show that DigitalOcean significantly outperforms the local VMware setup: TTFB was 128 ms versus 256 ms, LCP was 0.5 seconds versus 1.2 seconds, and the performance score reached 100 compared to 87. The superior performance is attributed to faster network connectivity, SSD storage, and optimized cloud infrastructure. In contrast, the VMware setup experienced higher latency due to local internet constraints. The study concludes that DigitalOcean is more suitable for production environments requiring high performance, while VMware Workstation remains ideal for local development and testing. These findings provide practical guidance for developers and administrators in selecting appropriate hosting platforms based on performance needs and resource constraints.